Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Effects of maternal arsenic exposure on birth outcomes using harmonized data across three birth cohorts - Zlatan Feric; Daniel Beene; Antonio J. Signes-Pastor; Deborah J. Watkins; Griffith Gao; Margaret R. Karagas; Debra A. MacKenzie; David R. Kaeli; Justin Manjourides (Toxicology and Environmental Health Sciences, 2026)
Objectives To assess the association between urinary arsenic concentrations and birth outcomes by harmonizing data from three independent birth cohorts. Methods We harmonized and analyzed data from the Navajo Birth Cohort Study (NBCS), the New Hampshire Birth Cohort Study (NHBCS), and the PROTECT Center study based on Puerto Rico. Birth outcomes of interest included birth weight, head circumference, birth length, gestational age at delivery, incidence of preterm birth, and size for gestational age. Urinary arsenic concentrations were used as the primary exposure metric. Harmonization involved aligning variable formats, adjusting for differences in laboratory methods, and excluding incompatible covariates, such as income and race. Results Harmonization increased the total sample size ( N = 3222) across cohorts. However, pooled analyses did not consistently demonstrate increased statistical power. Effect estimates for arsenic exposure were attenuated in some cases, and confidence intervals remained wide or even expanded relative to individual cohort analyses. Differences in biospecimen collection and laboratory assay methods required cohort-specific adjustments. Due to missing arsenic speciation data, the PROTECT cohort was excluded from two exposure models. Variability across cohorts limited the interpretability and precision of pooled estimates despite harmonization efforts. Conclusions While harmonizing data across multiple cohorts increased the sample size, it did not necessarily enhance statistical power or strengthen observed associations. Differences in data collection, laboratory methods, and available covariates posed significant challenges. These findings underscore the need for caution when interpreting pooled results from heterogeneous sources and highlight the importance of prospective planning for data harmonization in multi-cohort studies.

Age-related redistribution of zinc and copper within human skin - Nishat Zakaria; Alexander Griffiths; Clarisse Ganier; Magnus Lynch; David Messenger; Ranjit Bhogal; Wolfgang Maret (Journal of Trace Elements in Medicine and Biology, 2026)

Indigenous Perspectives on the Co-management of a Regional Conservation Area in the Peruvian Amazon - Natalia Arcos Cano; Michael P. Gilmore; Elizabeth Benson; Diego Valderrama; David Dimitrie; Brian M. Griffiths (Environmental Management, 2026)
Growing awareness of the critical role Indigenous Peoples and Local Communities (IPLCs) play in biodiversity conservation has underscored the need to shift conservation practices towards empowering IPLCs, supporting their land rights, traditional practices, and facilitating their political involvement. Despite IPLCs governing over 32% of global land, historically these communities have faced systemic marginalization and violence in the name of conservation. In response, international calls to action and policies have aimed to enhance IPLC participation in environmental governance through mechanisms like co-management. Adaptive Co-management (ACM) emerges as a promising approach, combining adaptive management’s flexibility with co-management’s collaborative principles. This study evaluates the ACM framework within the Maijuna-Kichwa Regional Conservation Area (MKRCA) in the Peruvian Amazon, established to protect the ancestral lands and biocultural resources of the Maijuna and Kichwa communities. Using a Community-Based Participatory Research (CBPR)-informed approach, we conducted interviews with 36 community members to assess their perspectives on the MKRCA’s co-management. Findings reveal significant improvements in resource abundance and community safety but also highlight issues with governmental support, communication, and equitable participation. Highly engaged participants voiced the strongest criticisms, underscoring how participation level shaped perceptions of governance. Recommendations were derived from participant perspectives but synthesized by the authors rather than fully co-developed. The study emphasizes the need for continuous evaluation and enhanced stakeholder engagement to optimize ACM’s effectiveness, offering culturally responsive recommendations to strengthen the MKRCA’s management and achieve its conservation objectives.

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Biochar reshapes soil bacterial community composition and survival strategies: a meta-analysis revealing trade-offs between microbial stability and functional complexity - Jianwei Li; Jeewani H. Peduruhewa; Robert W. Brown; David R. Chadwick; Robert I. Griffiths; Haoran Fu; Hongfeng Bian; LianXi Sheng; Qinqxu Ma; Davey L. Jones (Biology and Fertility of Soils, 2026)
As a promising strategy for improving soil health and mitigating climate change, biochar has received increasing attention in recent years. However, findings regarding its microbial effects are often context-dependent, and the complex impacts of biochar on soil microbial communities remain inadequately understood. Here, we integrated 843 samples of 16 S rRNA sequencing data from 24 independent studies, utilizing machine learning and co-occurrence network analysis to evaluate general patterns and mechanisms by which biochar alters bacteria community composition and survival strategies. Overall, biochar significantly increased soil organic C, total N, pH, and reduced bulk density, which in turn affected microbial communities. While biochar addition did not notably alter bacterial α-diversity (Shannon index or species richness), it significantly changed β-diversity, indicating that biochar addition altered microbial community composition. Biochar changed community composition and survival strategies by reducing the oligotroph/copiotroph ratio, favouring copiotrophs groups (e.g., Bacteroidota). K -strategists (e.g., Planctomycetota) were reduced by biochar, potentially due to increased nutrient availability and increased competition. Model selection analysis identified that soil physicochemical properties were key drivers of α-diversity, while climate variables were the main factors influencing β-diversity. Biochar properties represented key factors influencing changes in microbial survival strategy. Machine learning identified 138 biomarker genera, with biochar-treated soils showing an increase in Pseudomonadota. Co-occurrence network analysis indicated that biochar increased microbial stability, but reduced network complexity, suggesting a trade-off between resilience and functional redundancy following biochar addition. These findings provide new insights into how biochar influences the composition and ecological functions of soil bacterial communities and offer theoretical support for its scientific application in sustainable soil management.

Correction: Proposed highway in the Peruvian Amazon threatens vulnerable indigenous communities and natural protected areas - Brian M. Griffiths; David Dimitrie; Elizabeth Schierbeek; Edith Chinchilla Perez; Ellen Nirenblatt; Natalia Arcos Cano; Michael P. Gilmore (Ambio, 2026)

Quantifying changes in central Vietnam rainfall amount since the Late Pleistocene - Elizabeth W. Patterson; Alliya A. Akhtar; Michael L. Griffiths; David McGee; Quốc Đỗ-Trọng; Annabel Wolf; John A. Higgins; Stefania Gili; Mùi X. Trần; Hùng Q. Nguyễn; Trí H. Đinh; Thành N. Bùi; et al. (Earth and Planetary Science Letters, 2026)

Patterns and thresholds for soil pH across Europe in relation to soil health and degradation - Inma Lebron; Christopher J. Feeney; Sabine Reinsch; Nima Shokri; Mehdi H. Afshar; Steve Lofts; Rob Griffiths; David Fidler; Briony Jones; Panos Panagos; Kasia Sawicka; Aidan M. Keith; et al. (CATENA, 2025)

Before the brink: considering sublethal impacts of climate change on stingless bee flight performance - Carmen Rose Burke da Silva; Lachlan David Macnaughtan; Oliver William Griffith; Ajay Narendra (Journal of Thermal Biology, 2025)

Biodegradable mulch films exhibit slower-than-expected degradation with negligible effects on soil microbial communities - Martine Graf; Estelle Choiselat; Michaela K. Reay; Rafael Bargiela; Athanasios Dimitriou; Qiuyun Liu; Robert M. Elias; Peter N. Golyshin; Robert Griffiths; David R. Chadwick; Davey L. Jones (Journal of Hazardous Materials, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Ultrasound image abnormalities associated with the development of ovine pulmonary adenocarcinoma - David Collie; James Meehan; Helen Brown; Ziyuan Chang; Chris Cousens; Jo Moore; Helen Todd; David J. Griffiths; Nicole Storer; Chad E. Eckert; Mark Gray (Research in Veterinary Science, 2025)

Pollinator‐Promoting Interventions in European Urban Habitats—A Synthesis - Gabriella Süle; András Báldi; David Kleijn; Ingolf Steffan‐Dewenter; Stephen Venn; Dave Goulson; Simon Dietzel; Audrey Muratet; Lorna J. Cole; Erik Öckinger; Olga Tzortzakaki; Weronika Banaszak‐Cibicka; et al. (Ecology Letters, 2025)
Pollinators receive considerable interest due to their fundamental role in ecosystem functioning and human well‐being. Unlike farmlands, studies of urban pollinator‐promoting interventions are scarce and have not been synthesised, hampering policy implementation. To fill this gap, we compared pollinator‐promoting interventions (treatment) with conventionally managed (control) sites regarding vegetation, floral resources, and pollinators. Our synthesis investigated 1051 sampling sites with different interventions (abandonment, extensive mowing, flower sowing, and combined practices) and habitats (parks, grasslands, road verges, private and public gardens) from 28 European datasets at pooled‐ and study‐levels. Urban pollinator‐promoting interventions generally benefited plants and pollinators with taxon, intervention, habitat, and spatio‐temporal specific differences. Pooled analyses showed mostly positive and never negative treatment effects, while study‐level details described primarily positive and neutral but rarely negative effects. Bumblebees and butterflies benefited most from the interventions. Some effects were stronger for interventions involving flower sowing, interventions occurring in road verges, and interventions located in Northwestern Europe. Although regulations, guidelines, and monitoring are improving, knowledge gaps remain for some pollinator taxa (e.g., beetles), regions (e.g., Mediterranean), and novel interventions (e.g., for ground‐nesting insects). Further collaborative studies from around the world could help cities bring people, plants, and pollinators together by creating resilient, multi‐functional urban spaces.

Challenges and Opportunities in Monitoring and Mitigating Sea Turtle Bycatch in Tuna Regional Fisheries Management Organizations - Jose Carlos Baéz; Andrés Domingo; Hilario Murua; David Macías; Juan Antonio Camiñas; Francois Poisson; María José Juan Jorda; Jon López; Shane Griffiths; Marlon Roman; Martín Hall; Eric Gilman; et al. (Reviews in Fisheries Science & Aquaculture, 2025)

Association between organic micropollutants in tap water and human exposure and birth outcomes: Implications for environmental health in northern Puerto Rico - Yinmei Feng; Justin Manjourides; Stephanie L. Rich; Guangyu Li; Carmen Velez Vega; Ingrid Y. Padilla; Zaira Rosario-Pabón; Akram N. Alshawabkeh; Damian E. Helbling; Griffith Gao; David Kaeli; John D. Meeker; et al. (Journal of Hazardous Materials, 2025)

Speciation Rates of Freshwater Fish Across the Americas Vary With Environmental Heterogeneity and Dispersal Ability - David Griffiths (Journal of Biogeography, 2025)
Aims Species richnesses show marked spatial trends, but the contribution of speciation rates (SpecRates) to these trends is less clear. The roles of environmental heterogeneity (topography and climate), glaciation, dispersal ability, times to colonise, and to speciate to large‐scale variation in SpecRates of freshwater fish faunas are assessed. Location Atlantic and Pacific coast drainages in North, Central, and South America. Taxon Fish. Methods Published information was compiled on SpecRates, phylogenies, colonisation times, species geographic distributions, and migratory behaviour of fishes in 582 catchments. The effects of topographic and climatic factors, including glaciation and vagility, on three speciation rate metrics were examined using boosted regression tree models. Results Mean SpecRates differ five‐fold across drainage regions and with glaciation. Pacific coast drainage SpecRates are highest in the Nearctic and decline southwards, but in Atlantic drainages, rate trends differ between Nearctic and Neotropical basins. Assemblage SpecRates vary with the percentage of migratory species, glaciation, environmental heterogeneity, colonisation time, and species age. High Nearctic rates are associated with postglacial recolonisation by rapidly speciating diadromous species, but rates in the Neotropics for resident and potamodromous species are higher than for diadromous species. Species dispersing into an area are more migratory, occur further north, and have wider distributions than species diversifying in situ. Endemicity in the more recently colonised Nearctic increases with colonisation time to Neotropical levels. Main Conclusions Spatial and temporal variation in topography and climate generate differences in connectivity which, coupled with differences in species abilities to overcome these barriers, result in differences in speciation rates in different areas.

Proposed highway in the Peruvian Amazon threatens vulnerable indigenous communities and natural protected areas - Brian M. Griffiths; David Dimitrie; Elizabeth Schierbeek; Edith Chinchilla Perez; Ellen Nirenblatt; Natalia Arcos Cano; Michael P. Gilmore (Ambio, 2025)
The conservation of biocultural diversity in the Amazon rainforest has become an international priority in the face of global change. Megadevelopment projects threaten conservation efforts and the rights of Indigenous communities to manage their ancestral lands. We examine the potential impacts of one proposed highway development project in the Peruvian Amazon, the Bellavista-El Estrecho Highway, on local and Indigenous communities and natural protected areas in the region. We found that zones of influence of the proposed highway eclipse 343 Indigenous communities of at least 33 000 Indigenous people of ten distinct cultures, 43 503 km 2 of community land, and 26 210 km 2 of natural protected areas including the entirety of the Maijuna–Kichwa Regional Conservation Area and the unique high terrace ecosystems it holds. Under international and national law in Peru, Indigenous communities who will be affected by megadevelopment projects like this highway must be engaged in prior consultation.

Environmental risk factors for all-cause dementia, Alzheimer's disease dementia, vascular dementia, and mild cognitive impairment: An umbrella review and meta-analysis - Aaron Jones; Muhammad Usman Ali; Alexandra Mayhew; Komal Aryal; Rebecca H. Correia; Darly Dash; Derek R. Manis; Atiya Rehman; Megan E. O'Connell; Vanessa Taler; Andrew P. Costa; David B. Hogan; et al. (Environmental Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Mineralogic control on the calcium and magnesium stable isotopic compositions of modern microbial carbonates - Elizabeth M. Griffith; Matthew S. Fantle; Brittan V. Wogsland; Zijian Li; Majie Fan; David J. Wronkiewicz (Geochimica et Cosmochimica Acta, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Extremely low biodiversity Arctic intertidal habitats as sentinels for environmental change - Huw J. Griffiths; Catherine L. Waller; Stephen J. Roberts; Anna M. Jażdżewska; David S. Hik (Frontiers in Marine Science, 2024)
The Arctic is undergoing dramatic changes, including an unprecedented decline in sea ice. Previous studies have shown the severe structuring impact of sea ice scour upon polar intertidal communities. A dramatic example of the influence of Arctic sea ice is the highly depauperate intertidal of Cambridge Bay (Iqaluktuuttiaq) on Victoria Island, Nunavut, Canada. Cambridge Bay intertidal is dominated by a single species of amphipod crustacean, Gammarus setosus , with rare examples of another amphipod, bivalve molluscs, and oligochaetes. Primary producers are limited to a thin algal film, with no macroalgae present shallower than 2 m water depth. This intertidal biodiversity has remained extremely low since it was first surveyed 70 years ago, however, the seasonal sea ice thickness has been in decline for over 50 years. Given the observed dramatic increases in biodiversity and biomass with decreased sea ice cover elsewhere in the Arctic and the presence of the Canadian High Arctic Research Station, we suggest that the intertidal of Cambridge Bay offers an ideal location for a low cost, low effort, and long-term monitoring of biodiversity change and tipping points that may be influenced by sea ice loss in the Arctic as part of a network intertidal monitoring stations.

The legal and illegal supply chains of sea turtle eggs in Costa Rica - Helen Pheasey; Richard A. Griffiths; David L. Roberts (Environmental Development, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Neodymium isotope composition and rare earth element distribution of East Antarctic continental shelf and deep waters - Alex Griffiths; Myriam Lambelet; Kirsty Crocket; Richard Abell; Barry J. Coles; Katharina Kreissig; David Porter; Frank O. Nitsche; Mark Rehkämper; Tina van de Flierdt (Chemical Geology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

A data‐driven approach to multiple‐stressor impact assessment for a marine protected area - Laura L. Griffiths; Joel Williams; Christina A. Buelow; Vivitskaia J. Tulloch; Mischa P. Turschwell; Max D. Campbell; David Harasti; Rod M. Connolly; Christopher J. Brown (Conservation Biology, 2024)
The coastal environment is not managed in a way that considers the impact of cumulative threats, despite being subject to threats from all realms (marine, land, and atmosphere). Relationships between threats and species are often nonlinear; thus, current (linear) approaches to estimating the impact of threats may be misleading. We developed a data‐driven approach to assessing cumulative impacts on ecosystems and applied it to explore nonlinear relationships between threats and a temperate reef fish community. We used data on water quality, commercial fishing, climate change, and indicators of recreational fishing and urbanization to build a cumulative threat map of the northern region in New South Wales, Australia. We used statistical models of fish abundance to quantify associations among threats and biophysical covariates and predicted where cumulative impacts are likely to have the greatest impact on fish. We also assessed the performance of no‐take zones (NTZs), to protect fish from cumulative threats across 2 marine protected area networks (marine parks). Fishing had a greater impact on fish than water quality threats (i.e., percent increase above the mean for invertivores was 337% when fishing was removed and was 11% above the mean when water quality was removed inside NTZs), and fishing outside NTZs affected fish abundances inside NTZs. Quantifying the spatial influence of multiple threats enables managers to understand the multitude of management actions required to address threats.

Climate change disrupts the seasonal coupling of plant and soil microbial nutrient cycling in an alpine ecosystem - Arthur A. D. Broadbent; Lindsay K. Newbold; William J. Pritchard; Antonios Michas; Tim Goodall; Irene Cordero; Andrew Giunta; Helen S. K. Snell; Violette V. L. H. Pepper; Helen K. Grant; David X. Soto; Ruediger Kaufmann; et al. (Global Change Biology, 2024)
The seasonal coupling of plant and soil microbial nutrient demands is crucial for efficient ecosystem nutrient cycling and plant production, especially in strongly seasonal alpine ecosystems. Yet, how these seasonal nutrient cycling processes are modified by climate change and what the consequences are for nutrient loss and retention in alpine ecosystems remain unclear. Here, we explored how two pervasive climate change factors, reduced snow cover and shrub expansion, interactively modify the seasonal coupling of plant and soil microbial nitrogen (N) cycling in alpine grasslands, which are warming at double the rate of the global average. We found that the combination of reduced snow cover and shrub expansion disrupted the seasonal coupling of plant and soil N‐cycling, with pronounced effects in spring (shortly after snow melt) and autumn (at the onset of plant senescence). In combination, both climate change factors decreased plant organic N‐uptake by 70% and 82%, soil microbial biomass N by 19% and 38% and increased soil denitrifier abundances by 253% and 136% in spring and autumn, respectively. Shrub expansion also individually modified the seasonality of soil microbial community composition and stoichiometry towards more N‐limited conditions and slower nutrient cycling in spring and autumn. In winter, snow removal markedly reduced the fungal:bacterial biomass ratio, soil N pools and shifted bacterial community composition. Taken together, our findings suggest that interactions between climate change factors can disrupt the temporal coupling of plant and soil microbial N‐cycling processes in alpine grasslands. This could diminish the capacity of these globally widespread alpine ecosystems to retain N and support plant productivity under future climate change.

Coastal boulder movement on a rocky shoreline in northwest Ireland from repeat UAV surveys using Structure from Motion photogrammetry - Jasper Knight; Helene Burningham; David Griffiths; Yao Yao (Geomorphology, 2023)

Effects of a mediterranean diet on the gut microbiota and microbial metabolites: A systematic review of randomized controlled trials and observational studies - Rachel Kimble; Phebee Gouinguenet; Ammar Ashor; Christopher Stewart; Kevin Deighton; Jamie Matu; Alex Griffiths; Fiona C. Malcomson; Abraham Joel; David Houghton; Emma Stevenson; Anne Marie Minihane; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Sparing old-growth maximises conservation outcomes within selectively logged Amazonian rainforest - Gianluca Cerullo; Filipe França; Tom Finch; Philip Erm; Hannah Griffiths; Julio Louzada; Chris G. Bousfield; Mike R. Massam; Carlos A. Peres; Jos Barlow; Rhys E. Green; David P. Edwards; et al. (Biological Conservation, 2023)

The offshore renewables industry may be better served by new bespoke design guidelines than by automatic adoption of recommended practices developed for oil and gas infrastructure: A recommendation illustrated by subsea cable design - Terry Griffiths; Scott Draper; Liang Cheng; Hongwei An; Marie-Lise Schläppy; Antonino Fogliani; David White; Stuart Noble; Daniel Coles; Fraser Johnson; Bryan Thurstan; Yunfei Teng (Frontiers in Marine Science, 2023)
Introduction There is an emerging need for the offshore renewable industry to have their own bespoke design guidelines because the associated projects and offshore facilities differ in fundamental ways to oil and gas facilities. Offshore renewable energy (ORE) facilities have already surpassed the numbers of installed facilities in the oil and gas industry by an order of magnitude and demand is forecast to continue growing exponentially. In addition ORE facilities often have different response characteristics and limit states or failure modes as well as profoundly different risk and consequence profiles given they are generally uncrewed and do not contain explosive hydrocarbon fluids which might be released into the environment. Therefore, the purpose of this paper is to advocate for licensing bodies and regulators (such as the various national PEL 114 committees) to challenge the process of automatic adoption of oil and gas design processes, while pushing for offshore renewables to be treated differently, when appropriate, with more relevant and applicable guidance. Methods To support this argument we present new bespoke design guidance developed for subsea cables based on specific modes of cable behaviour, which often differ from pipelines. We also show worked examples from recent project experience. The results from on-bottom stability analyses of a set of cables are compared between conventional oil and gas guidance following DNV-RP-F109 versus the stability using cable-optimised approaches. Results The outcomes from the ‘conventional’ oil and gas results are not simply biased compared to cable-optimised design methods, with a trend of being either conservative or unconservative. Instead, the results of the two methods are very poorly correlated. This shows that the oil and gas approach isn't simply biased when applied to cables, but is instead unreliable because it doesn't capture the underlying failure conditions. These analytical comparisons are supported by field observation - the ocean doesn't lie, and makes short work of any anthropogenic structures which are designed with inadequate appreciation of the real world conditions. Discussion To support the rapid growth of ORE, we should therefore actively pursue opportunities to rewrite the design rules and standards, so that they better support the specific requirements of ORE infrastructure, rather than legacy oil and gas structures. With more appropriate design practices, we can accelerate the roll out of ORE to meet net zero, and mitigate the climate crisis.

Genome-wide identification and functional prediction of silicon (Si) transporters in poplar (Populus trichocarpa) - Md Mahmudul Hassan; Samir Martin; Kai Feng; Timothy B. Yates; Guoliang Yuan; Madhavi Z. Martin; Stanton Martin; Wellington Muchero; Natalie A. Griffiths; David J. Weston; Xiaohan Yang (Plant Biotechnology Reports, 2023)
Silicon (Si) enhances plant tolerance to various biotic and abiotic stressors such as salinity, drought, and heat. In addition, Si can be biomineralized within plants to form organic carbon-containing phytoliths that can have ecosystem-level consequences by contributing to long-term carbon sequestration. Si is taken up and transported in plants via different transporter proteins such as influx transporters (e.g., Lsi1, Lsi6) and efflux transporters (e.g., Lsi2). Additionally, the imported Si can be deposited in plant leaves via silicification process using the Siliplant 1 (e.g., Slp1) protein. Functional homologs of these proteins have been reported in different food crops. Here, we performed a genome-wide analysis to identify different Si transporters and Slp1 homologs in the bioenergy crop poplar ( Populus trichocarpa Torr. and A. Gray ex W. Hook). We identified one channel-type Si influx transporter (PtLsi1; Potri.017G083300), one Si efflux transporter (PtLsi2; Potri.012G144000) and two proteins like Slp1 (PtSlp1a; Potri.004G168600 and PtSlp1b; Potri.009G129900 ) in the P. trichocarpa genome. We found a unique sequence (KPKPPVFKPPPVPI) in PtSlp1a which is repeated six times. Repeated presence of this sequence in PtSlp1a indicates that this protein might be important for silicification processes in P. trichocarpa. The mutation profiles of different Si transporters in a P. trichocarpa genome-wide association study population identified significant and impactful mutations in Potri.004G168600 and Potri.009G129900 . Using a publically accessible database ( http://bar.utoronto.ca/eplant_poplar/ ), digital expression analysis of the putative Si transporters in P. trichocarpa found low to moderate expression in the anticipated tissues, such as roots and leaves. Subcellular localization analysis found that PtLsi1/PtLsi2 are localized in the plasma membrane, whereas PtSlp1a/PtSlp1b are found in the extracellular spaces. Protein–Protein interaction analysis of PtLsi1/PtLsi2 identified Delta-1-pyrroline-5-carboxylate synthase (P5CS) as one of the main interacting partners of PtLsi2, which plays a key role in proline biosynthesis. Proline is a well-known participant in biotic and abiotic stress tolerance in plants. These findings will reinforce future efforts to modify Si accumulation for enhancing plant stress tolerance and carbon sequestration in poplar.

Relationship between coliphage and Enterococcus at southern California beaches and implications for beach water quality management - Amity G. Zimmer-Faust; John F. Griffith; Joshua A. Steele; Bryan Santos; Yiping Cao; Laralyn Asato; Tania Chiem; Samuel Choi; Arturo Diaz; Joe Guzman; David Laak; Michele Padilla; et al. (Water Research, 2023)

Atmospheric concentrations and sources of black carbon over tropical Australian waters - Changda Wu; Haydn Trounce; Erin Dunne; David W.T. Griffith; Scott D. Chambers; Alastair G. Williams; Ruhi S. Humphries; Luke T. Cravigan; Branka Miljevic; Chunlin Zhang; Hao Wang; Boguang Wang; et al. (Science of The Total Environment, 2023)

What causes energy and transport poverty in Ireland? Analysing demographic, economic, and social dynamics, and policy implications - Christopher Lowans; Aoife Foley; Dylan Furszyfer Del Rio; Brian Caulfield; Benjamin K. Sovacool; Steven Griffiths; David Rooney (Energy Policy, 2023)

Patient–Specific Immersed Finite Element–Difference Model of Transcatheter Aortic Valve Replacement - Jordan A. Brown; Jae H. Lee; Margaret Anne Smith; David R. Wells; Aaron Barrett; Charles Puelz; John P. Vavalle; Boyce E. Griffith (Annals of Biomedical Engineering, 2023)
Transcatheter aortic valve replacement (TAVR) first received FDA approval for high-risk surgical patients in 2011 and has been approved for low-risk surgical patients since 2019. It is now the most common type of aortic valve replacement, and its use continues to accelerate. Computer modeling and simulation (CM&S) is a tool to aid in TAVR device design, regulatory approval, and indication in patient-specific care. This study introduces a computational fluid-structure interaction (FSI) model of TAVR with Medtronic’s CoreValve Evolut R device using the immersed finite element-difference (IFED) method. We perform dynamic simulations of crimping and deployment of the Evolut R, as well as device behavior across the cardiac cycle in a patient-specific aortic root anatomy reconstructed from computed tomography (CT) image data. These IFED simulations, which incorporate biomechanics models fit to experimental tensile test data, automatically capture the contact within the device and between the self-expanding stent and native anatomy. Further, we apply realistic driving and loading conditions based on clinical measurements of human ventricular and aortic pressures and flow rates to demonstrate that our Evolut R model supports a physiological diastolic pressure load and provides informative clinical performance predictions.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Bushfire smoke plume composition and toxicological assessment from the 2019–2020 Australian Black Summer - Jack B. Simmons; Clare Paton-Walsh; Asher P. Mouat; Jennifer Kaiser; Ruhi S. Humphries; Melita Keywood; David W. T. Griffith; Adhitya Sutresna; Travis Naylor; Jhonathan Ramirez-Gamboa (Air Quality, Atmosphere & Health, 2022)
Many of the population centres in southeast Australia were swathed in bushfire smoke during the 2019–2020 austral summer. Bushfires burning during what is now known as the Black Summer was historically large and severe, and the fire season historically long. The chemical composition in the gas and aerosol phase of aged plumes measured near Wollongong, NSW in early 2020 is reported in this work. Enhancement ratios to carbon monoxide are presented for thirteen species (acetaldehyde, acetone, acetonitrile, black carbon aerosol, benzene, methane, methacrolein + methyl vinyl ketone, methyl ethyl ketone, methanol, ammonium ion PM 1 fraction, nitrate ion PM 1 fraction, organic PM 1 fraction and PM 2.5 ). Observed plume composition is comparable to that measured in fresh smoke from Australian fires reported in the literature. Enhancements of biogenic volatile organic compounds such as isoprene (smoke-effected period mean 1 ppb, maximum 6 ppb) were observed along with elevated concentrations of particulate variables. Enhancement ratios reported here can be used in plume modelling of landscape-scale fires and assist in concentration estimates of infrequently measured atmospheric pollutants. The relative toxicological contribution of species present in the plumes was determined for plume exposure at the measurement site and for concentrated plumes at a population centre case study. Similar results were apparent at both locations. Contributions to the toxicological loading were dominated by respirable particles (~ 52–63% total contribution), formaldehyde (~ 30–39% total contribution) and acrolein. This is a reminder to consider the toxicological contributions in the gas phase when considering health impacts of population exposure to bushfire smoke.

Long-Term Drought and Warming Alter Soil Bacterial and Fungal Communities in an Upland Heathland - Fiona M. Seaton; Sabine Reinsch; Tim Goodall; Nicola White; Davey L. Jones; Robert I. Griffiths; Simon Creer; Andy Smith; Bridget A. Emmett; David A. Robinson (Ecosystems, 2022)
The response of soil microbial communities to a changing climate will impact global biogeochemical cycles, potentially leading to positive and negative feedbacks. However, our understanding of how soil microbial communities respond to climate change and the implications of these changes for future soil function is limited. Here, we assess the response of soil bacterial and fungal communities to long-term experimental climate change in a heathland organo-mineral soil. We analysed microbial communities using Illumina sequencing of the 16S rRNA gene and ITS2 region at two depths, from plots undergoing 4 and 18 years of in situ summer drought or warming. We also assessed the colonisation of Calluna vulgaris roots by ericoid and dark septate endophytic (DSE) fungi using microscopy after 16 years of climate treatment. We found significant changes in both the bacterial and fungal communities in response to drought and warming, likely mediated by changes in soil pH and electrical conductivity. Changes in the microbial communities were more pronounced after a longer period of climate manipulation. Additionally, the subsoil communities of the long-term warmed plots became similar to the topsoil. Ericoid mycorrhizal colonisation decreased with depth while DSEs increased; however, these trends with depth were removed by warming. We largely ascribe the observed changes in microbial communities to shifts in plant cover and subsequent feedback on soil physicochemical properties, especially pH. Our results demonstrate the importance of considering changes in soil microbial responses to climate change across different soil depths and after extended periods of time.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Do the drivers and levels of isolation in fish faunas differ across Atlantic and Pacific drainages in the Americas? - David Griffiths (Journal of Biogeography, 2022)
Aim The roles of physical barriers to dispersal and species' abilities to cross barriers have in shaping freshwater fish distributions has been little explored at the macroscale. This study investigates how topography and species migratory behaviours and salinity tolerances (vagility) affect catchment isolation, species richness, large‐scale distribution patterns and turnover across latitudes and coasts. Location North (NAm), Middle (MAm) and South (SAm) America. Taxon Fish. Methods From a large, published, dataset Pacific and Atlantic coast catchments in NAm, MAm and SAm were allocated to six georegions and species richness and composition correlated with information on catchment size, channel gradient and discharge. Catchment species richnesses, species–area relations (SAR), endemicity and turnover relationships were examined across coasts and latitude for species with different migratory behaviours and salinity tolerances. Results Pacific coast rivers are smaller, steeper, hydrologically more variable and have narrower marine shelves than Atlantic ones, except in MAm. Catchment isolation is greater in Pacific drainages but the barriers to species exchange differ across georegions. Species richnesses are greater in Atlantic drainages but the proportion of vagile species is smaller. SAR slopes are flatter in vagile species and endemicity less. Turnover varies with catchment topography, the relative contribution of vagile species and, in MAm, on evolutionary history. Main conclusions Tectonic and geomorphic processes influence catchment size and topography, and along with species differences in dispersal potential, affect how isolated catchments are, with consequences for species richness and composition.

Lessons learnt from Typhoons Fitow and In-Fa: implications for improving urban flood resilience in Asian Coastal Cities - Faith Ka Shun Chan; Xinbing Gu; Yunfei Qi; Dimple Thadani; Yongqin David Chen; Xiaohui Lu; Lei Li; James Griffiths; Fangfang Zhu; Jianfeng Li; Wendy Y. Chen (Natural Hazards, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Shrub expansion modulates belowground impacts of changing snow conditions in alpine grasslands - Arthur A. D. Broadbent; Michael Bahn; William J. Pritchard; Lindsay K. Newbold; Tim Goodall; Andrew Guinta; Helen S. K. Snell; Irene Cordero; Antonios Michas; Helen K. Grant; David X. Soto; Rüdiger Kaufmann; et al. (Ecology Letters, 2022)
Climate change is disproportionately impacting mountain ecosystems, leading to large reductions in winter snow cover, earlier spring snowmelt and widespread shrub expansion into alpine grasslands. Yet, the combined effects of shrub expansion and changing snow conditions on abiotic and biotic soil properties remains poorly understood. We used complementary field experiments to show that reduced snow cover and earlier snowmelt have effects on soil microbial communities and functioning that persist into summer. However, ericaceous shrub expansion modulates a number of these impacts and has stronger belowground effects than changing snow conditions. Ericaceous shrub expansion did not alter snow depth or snowmelt timing but did increase the abundance of ericoid mycorrhizal fungi and oligotrophic bacteria, which was linked to decreased soil respiration and nitrogen availability. Our findings suggest that changing winter snow conditions have cross‐seasonal impacts on soil properties, but shifts in vegetation can modulate belowground effects of future alpine climate change.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Novel compound heterozygous missense mutations in GDAP1 cause Charcot–Marie–Tooth type 4A - HUIQIN XUE; NEVEN MAKSEMOUS; DAVID SIDHOM; LAN MA; SHAOHUI CHEN; JIANRUI WU; YU FENG; LARISA M. HAUPT; LYN R. GRIFFITHS (Journal of Genetics, 2021)

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Evaluating the congruence between DNA ‐based and morphological taxonomic approaches in water and sediment trap samples: Analyses of a 36‐month time series from a temperate monomictic lake - Joanna Gauthier; David Walsh; Daniel T. Selbie; Alyssa Bourgeois; Katherine Griffiths; Isabelle Domaizon; Irene Gregory‐Eaves (Limnology and Oceanography, 2021)
Paleolimnological studies are central for identifying long‐term changes, yet many studies rely on bioindicators that deposit detectable subfossils in sediments, such as diatoms and cladocerans. Emerging DNA‐based approaches are expanding the taxonomic diversity that can be investigated. However, as sedimentary DNA‐based approaches are expanding rapidly, calibration work is required to determine the advantages and limitations of these techniques. In this study, we assessed the congruence between morphological and DNA‐based approaches applied to sediment trap samples for diatoms and crustaceans using both intracellular and extracellular DNA. We also evaluated which taxa are deposited in sediment traps from the water column to identify potential paleolimnological bioindicators of environmental variations. Based on 18S rRNA gene amplicons, we developed and analyzed a micro‐eukaryotic, monthly time series that spanned 3 years and was comprised of paired water column and sediment trap samples from Cultus Lake, British Columbia, Canada. Comparisons of assemblages derived from our genetic and morphological analyses using RV coefficients revealed significant correlations for diatoms, but weaker correlations for crustaceans. Intracellular DNA reads correlated more strongly with diatom morphology, while extracellular DNA reads correlated more strongly with crustacean morphology. Additional analyses of amplicon sequence variants shared between water and sediment trap samples revealed a wide diversity of taxa to study in paleolimnology, including Ciliophora, Dinoflagellata, Chytridiomycota, Chrysophyceae, and Cryptophyceae. Partial RDAs identified significant environmental predictors of these shared assemblages. Overall, our study demonstrates the effectiveness of DNA‐based approaches to track community dynamics from sediment samples, an essential step for successful paleolimnological studies.

Building a bridge between adaptive capacity and adaptive potential to understand responses to environmental change - Travis Seaborn; David Griffith; Andrew Kliskey; Christopher C. Caudill (Global Change Biology, 2021)
Adaptive capacity is a topic at the forefront of environmental change research with roots in both social, ecological, and evolutionary science. It is closely related to the evolutionary biology concept of adaptive potential. In this systematic literature review, we: (1) summarize the history of these topics and related fields; (2) assess relationship(s) between the concepts among disciplines and the use of the terms in climate change research, and evaluate methodologies, metrics, taxa biases, and the geographic scale of studies; and (3) provide a synthetic conceptual framework to clarify concepts. Bibliometric analyses revealed the terms have been used most frequently in conservation and evolutionary biology journals, respectively. There has been a greater growth in studies of adaptive potential than adaptive capacity since 2001, but a greater geographical extent of adaptive capacity studies. Few studies include both, and use is often superficial. Our synthesis considers adaptive potential as one process contributing to adaptive capacity of complex systems, notes “sociological” adaptive capacity definitions include actions aimed at desired outcome (i.e., policies) as a system driver whereas “biological” definitions exclude such drivers, and suggests models of adaptive capacity require integration of evolutionary and social–ecological system components.

Yellowfin Tuna Behavioural Ecology and Catchability in the South Atlantic: The Right Place at the Right Time (and Depth) - Serena R. Wright; David Righton; Joachim Naulaerts; Robert J. Schallert; Chris A. Griffiths; Taylor Chapple; Daniel Madigan; Vladimir Laptikhovsky; Victoria Bendall; Rhys Hobbs; Doug Beare; Elizabeth Clingham; et al. (Frontiers in Marine Science, 2021)
The yellowfin tuna ( Thunnus albacares: YFT) is a widely distributed, migratory species that supports valuable commercial fisheries. Landings of YFT are seasonally and spatially variable, reflecting changes in their availability and accessibility to different fleets and metiers which, in turn, has implications for sustainable management. Understanding the dynamics of YFT behaviour and how it is affected by biological and ecological factors is therefore of consequence to fisheries management design. Archival and pop-up satellite tags (PSAT) were used in the South Atlantic Ocean around St Helena between 2015 and 2020 to collect information on the movements, foraging and locomotory behaviour of YFT. The study aimed to (1) identify vertical behaviour of YFT within St Helena’s EEZ; (2) assess the timing and depth of potential feeding events and (3) to use the information to inform on the catchability of YFT to the local pole and line fishing fleet. Results indicate that the YFT daytime behaviour shifted between shallow with high incidence of fast starts in surface waters in summer months (December to April), to deep with high incidence of strikes at depth in colder months (May to November). Catchability of YFT was significantly reduced between May and November as YFT spent more time at depths below 100 m during the day, which coincides with a reduction in the quantity of YFT caught by the inshore fleet.

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

Carbon flux and forest dynamics: Increased deadwood decomposition in tropical rainforest tree‐fall canopy gaps - Hannah M. Griffiths; Paul Eggleton; Nicole Hemming‐Schroeder; Tom Swinfield; Joel S. Woon; Steven D. Allison; David A. Coomes; Louise A. Ashton; Catherine L. Parr (Global Change Biology, 2021)
Tree mortality rates are increasing within tropical rainforests as a result of global environmental change. When trees die, gaps are created in forest canopies and carbon is transferred from the living to deadwood pools. However, little is known about the effect of tree‐fall canopy gaps on the activity of decomposer communities and the rate of deadwood decay in forests. This means that the accuracy of regional and global carbon budgets is uncertain, especially given ongoing changes to the structure of rainforest ecosystems. Therefore, to determine the effect of canopy openings on wood decay rates and regional carbon flux, we carried out the first assessment of deadwood mass loss within canopy gaps in old‐growth rainforest. We used replicated canopy gaps paired with closed canopy sites in combination with macroinvertebrate accessible and inaccessible woodblocks to experimentally partition the relative contribution of microbes vs. termites to decomposition within contrasting understorey conditions. We show that over a 12 month period, wood mass loss increased by 63% in canopy gaps compared with closed canopy sites and that this increase was driven by termites. Using LiDAR data to quantify the proportion of canopy openings in the study region, we modelled the effect of observed changes in decomposition within gaps on regional carbon flux. Overall, we estimate that this accelerated decomposition increases regional wood decay rate by up to 18.2%, corresponding to a flux increase of 0.27 Mg C ha −1 year −1 that is not currently accounted for in regional carbon budgets. These results provide the first insights into how small‐scale disturbances in rainforests can generate hotspots for decomposer activity and carbon fluxes. In doing so, we show that including canopy gap dynamics and their impacts on wood decomposition in forest ecosystems can help improve the predictive accuracy of the carbon cycle in land surface models.

Transforming sustainability science for practice: a social–ecological systems framework for training sustainability professionals - Andrew Kliskey; Lilian Alessa; David Griffith; Sarah Olsen; Paula Williams; Sammy Matsaw; Martin Cenek; Jim Gosz; Sarah Dengler (Sustainability Science, 2021)

The Utility of Satellites and Autonomous Remote Sensing Platforms for Monitoring Offshore Aquaculture Farms: A Case Study for Canopy Forming Kelps - Tom W. Bell; Nick J. Nidzieko; David A. Siegel; Robert J. Miller; Kyle C. Cavanaugh; Norman B. Nelson; Daniel C. Reed; Dmitry Fedorov; Christopher Moran; Jordan N. Snyder; Katherine C. Cavanaugh; Christie E. Yorke; et al. (Frontiers in Marine Science, 2020)
The emerging sector of offshore kelp aquaculture represents an opportunity to produce biofuel feedstock to help meet growing energy demand. Giant kelp represents an attractive aquaculture crop due to its rapid growth and production, however precision farming over large scales is required to make this crop economically viable. These demands necessitate high frequency monitoring to ensure outplant success, maximum production, and optimum quality of harvested biomass, while the long distance from shore and large necessary scales of production makes in person monitoring impractical. Remote sensing offers a practical monitoring solution and nascent imaging technologies could be leveraged to provide daily products of the kelp canopy and subsurface structures over unprecedented spatial scales. Here, we evaluate the efficacy of remote sensing from satellites and aerial and underwater autonomous vehicles as potential monitoring platforms for offshore kelp aquaculture farms. Decadal-scale analyses of the Southern California Bight showed that high offshore summertime cloud cover restricts the ability of satellite sensors to provide high frequency direct monitoring of these farms. By contrast, daily monitoring of offshore farms using sensors mounted to aerial and underwater drones seems promising. Small Unoccupied Aircraft Systems (sUAS) carrying lightweight optical sensors can provide estimates of canopy area, density, and tissue nitrogen content on the time and space scales necessary for observing changes in this highly dynamic species. Underwater color imagery can be rapidly classified using deep learning models to identify kelp outplants on a longline farm and high acoustic returns of kelp pneumatocysts from side scan sonar imagery signal an ability to monitor the subsurface development of kelp fronds. Current sensing technologies can be used to develop additional machine learning and spectral algorithms to monitor outplant health and canopy macromolecular content, however future developments in vehicle and infrastructure technologies are necessary to reduce costs and transcend operational limitations for continuous deployment in an offshore setting.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Foraging habitat determines predator–prey size relationships in marine fishes - David Griffiths (Journal of Fish Biology, 2020)
Predator–prey size (PPS) relationships are determined by predator behaviour, with the likelihood of prey being eaten dependent on their size relative to that of the consumer. Published PPS relationships for 30 pelagic or benthic marine fish species were analysed using quantile regression to determine how median, lower and upper prey sizes varied with predator size and habitat. Habitat effects on predator foraging activity/mode, morphology, growth and natural mortality are quantified and the effects on PPS relationships explored. Pelagic species are more active, more likely to move by caudal fin propulsion and grow more rapidly but have higher mortality rates than benthic species, where the need for greater manoeuvrability when foraging in more physically complex habitats favours ambush predators using pectoral fin propulsion. Prey size increased with predator size in most species, but pelagic species ate relatively smaller prey than benthic predators. As pelagic predators grew, lower prey size limits changed little, and prey size range increased but median relative prey size declined, whereas the lower limit increased and median relative prey size was constant or increased in benthic species.

Environmental Change and Human Migration: Stylized Facts from Puerto Rico and Honduras - David Griffith (Coastal Management, 2020)

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Tropical Coastal Wetlands Ameliorate Nitrogen Export During Floods - Maria Fernanda Adame; Melanie E. Roberts; David P. Hamilton; Christopher E. Ndehedehe; Vanessa Reis; Jing Lu; Matthew Griffiths; Graeme Curwen; Mike Ronan (Frontiers in Marine Science, 2019)

Maternal versus artificial rearing shapes the rumen microbiome having minor long‐term physiological implications - Alejandro Belanche; David R. Yáñez‐Ruiz; Andrew P. Detheridge; Gareth W. Griffith; Alison H. Kingston‐Smith; Charles J. Newbold (Environmental Microbiology, 2019)
Summary Increasing productivity is a key target in ruminant science which requires better understanding of the rumen microbiota. This study investigated how maternal versus artificial rearing shapes the rumen microbiota using 24 sets of triplet lambs. Lambs within each sibling set were randomly assigned to natural rearing on the ewe (NN); ewe colostrum for 24 h followed by artificial milk feeding (NA); and colostrum alternative and artificial milk feeding (AA). Maternal colostrum feeding enhanced VFA production at weaning but not thereafter. At weaning, lambs reared on milk replacer had no rumen protozoa and lower microbial diversity, whereas natural rearing accelerated the rumen microbial development and facilitated the transition to solid diet. Differences in the rumen prokaryotic communities disappear later in life when all lambs were grouped on the same pasture up to 23 weeks of age. However, NN animals retained higher fungal diversity and abundances of Piromyces , Feramyces and Diplodiniinae protozoa as well as higher feed digestibility (+4%) and animal growth (+6.5%) during the grazing period. Nevertheless, no correlations were found between rumen microbiota and productive outcomes. These findings suggest that the early life nutritional intervention determine the initial rumen microbial community, but the persistence of these effects later in life is weak.

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Pre-treatment with microRNA-181a Antagomir Prevents Loss of Parvalbumin Expression and Preserves Novel Object Recognition Following Mild Traumatic Brain Injury - Brian B. Griffiths; Peyman Sahbaie; Anand Rao; Oiva Arvola; Lijun Xu; Deyong Liang; Yibing Ouyang; David J. Clark; Rona G. Giffard; Creed M. Stary (NeuroMolecular Medicine, 2019)

Comparison of Unyvero P55 Pneumonia Cartridge, in-house PCR and culture for the identification of respiratory pathogens and antibiotic resistance in bronchoalveolar lavage fluids in the critical care setting - Naomi J. Gadsby; Martin P. McHugh; Callum Forbes; Laura MacKenzie; Stephen K. D. Hamilton; David M. Griffith; Kate E. Templeton (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

An assessment of areal and transect-based historic shoreline changes in the context of coastal planning - David Griffiths; Chris House; Nelson Rangel-Buitrago; Tony Thomas (Journal of Coastal Conservation, 2019)

Correction to: Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Genome Sequence Analysis of Two Pseudomonas putida Strains to Identify a 17-Hydroxylase Putatively Involved in Sparteine Degradation - Andrew P. Detheridge; Gareth W. Griffith; David J. Hopper (Current Microbiology, 2018)

Climate and soils together regulate photosynthetic carbon isotope discrimination within C 3 plants worldwide - William K. Cornwell; Ian J. Wright; Joel Turner; Vincent Maire; Margaret M. Barbour; Lucas A. Cernusak; Todd Dawson; David Ellsworth; Graham D. Farquhar; Howard Griffiths; Claudia Keitel; Alexander Knohl; et al. (Global Ecology and Biogeography, 2018)
Aim Within C 3 plants, photosynthesis is a balance between CO 2 supply from the atmosphere via stomata and demand by enzymes within chloroplasts. This process is dynamic and a complex but crucial aspect of photosynthesis. We sought to understand the spatial pattern in CO 2 supply–demand balance on a global scale, via analysis of stable isotopes of carbon within leaves (Δ 13 C), which provide an integrative record of CO 2 drawdown during photosynthesis. Location Global Time period 1951–2011. Major taxa studied Vascular plants. Methods We assembled a database of leaf carbon isotope ratios containing 3,979 species–site combinations from across the globe, including 3,645 for C 3 species. We examined a wide array of potential climate and soil drivers of variation in Δ 13 C. Results The strongest drivers of carbon isotope discrimination at the global scale included atmospheric pressure, potential evapotranspiration and soil pH, which explained 44% of the variation in Δ 13 C. Addition of eight more climate and soil variables (each explaining small but highly significant amounts of variation) increased the explained variation to 60%. On top of this, the largest plant trait effect was leaf nitrogen per area, which explained 11% of Δ 13 C variation. Main conclusions: By considering variation in Δ 13 C at a considerably larger scale than previously, we were able to identify and quantify key drivers in CO 2 supply–demand balance previously unacknowledged. Of special note is the key role of soil properties, with greater discrimination on low‐pH and high‐silt soils. Unlike other plant traits, which show typically wide variation within sets of coexisting species, the global pattern in carbon stable isotope ratios is much more conservative; there is relatively narrow variation in time‐integrated CO 2 concentrations at the site of carboxylation among plants in a given soil and climate.

Why does freshwater fish species richness differ between Pacific and Atlantic drainages of the Americas? - David Griffiths (Journal of Biogeography, 2018)
Aim To identify the contributions of geomorphological and hydrological/climatic factors to differences in total and endemic freshwater fish species richness between Atlantic and Pacific drainages. Location Glaciated and unglaciated catchments draining to the Atlantic and Pacific Oceans in North ( NA ) and South America ( SA ). Taxon Fish. Methods A database of native freshwater fish species richnesses in drainage basins was compiled from published information, and the contributions of temperature, rainfall, catchment area, river length, channel gradient, discharge and geographic location in accounting for variation in total and endemic species richness were assessed using boosted regression trees. Results Atlantic drainages have larger catchments, with longer rivers, lower channel gradients, greater discharges and lower flow variability than Pacific ones of the same size. Unglaciated Atlantic drainages in both NA and SA have more species than Pacific drainages, but glaciated Pacific NA had significantly more species than the other Pacific areas. Geographic location had the greatest influence on total richness, but catchment area, river length and temperature were more important for endemic species. Pacific drainages had proportionally more endemics than Atlantic drainages. Main conclusions Tectonically driven topographic change, by altering relief, affects catchment size, slopes and connectivity, with the latter also affected by climatic changes in ice cover and aridity. These geomorphic and long‐term climatic changes, by influencing speciation, extinction and dispersal, govern freshwater fish species richness in Atlantic and Pacific catchments.

Mollusc species richness and abundance from shelf to abyssal depths in the Ross Sea (Antarctica): the importance of fine-mesh-towed gears and implications for future sampling - Claudio Ghiglione; Maria Chiara Alvaro; Paola Piazza; David Bowden; Huw J. Griffiths; Cinzia Carota; Consuelo R. Nava; Stefano Schiaparelli (Polar Biology, 2017)

Connectivity and vagility determine beta diversity and nestedness in North American and European freshwater fish - David Griffiths (Journal of Biogeography, 2017)
Aim This study assesses the extent to which biogeographic patterns in freshwater fish beta diversity and nestedness are due to dispersal limitation, from differences in dispersal opportunity across geographic areas and in dispersal ability across species. Location Europe and the Atlantic and Pacific realms of North America ( NA ), east and west of the Continental Divide. Methods The effects of glaciation, realm shape, connectivity, current climate and vagility on regional‐level beta diversity and nestedness were investigated. Turnover and nestedness‐resultant dissimilarity components of beta diversity and the nestedness metric based on overlap and decreasing fill ( NODF ) were calculated from regional species lists and the contributions of turnover and segregation to nestedness structure quantified. Results Geographic distance was a stronger predictor of beta diversity than climatic and environmental heterogeneity distances. Species range shapes varied with postglacial colonization direction, being more extensive in an east–west direction in Europe than in Atlantic NA . Turnover increased with declining connectivity, in unglaciated areas, and in non‐migratory species. Species were significantly less nested than expected because of high turnover and within‐realm heterogeneity in regional faunas. Deviations from nestedness were greater in unglaciated areas and in migratory species. Non‐migrants, but not migrants, exhibited coincident range boundaries. Main conclusions Spatial trends in beta diversity and nestedness in freshwater fish in NA and Europe result primarily from differences in postglacial recolonization opportunity across realms and in dispersal ability across species. Multiple metrics are necessary to identify the processes determining the spatial structure of species assemblages.

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Identification and Potential Regulatory Properties of Evolutionary Conserved Regions (ECRs) at the Schizophrenia-Associated MIR137 Locus - Olympia Gianfrancesco; Daniel Griffiths; Paul Myers; David A. Collier; Vivien J. Bubb; John P. Quinn (Journal of Molecular Neuroscience, 2016)

Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2016)
Skates and rays constitute the most speciose group of chondrichthyan fishes, yet are characterised by remarkable levels of morphological and ecological conservatism. They can be challenging to identify, which makes monitoring species compositions for fisheries management purposes problematic. Owing to their slow growth and low fecundity, skates are vulnerable to exploitation and species exhibiting endemism or limited ranges are considered to be the most at risk. The Madeira skate Raja maderensis is endemic and classified as ‘Data Deficient’ by the IUCN, yet its taxonomic distinctiveness from the morphologically similar and more wide-ranging thornback ray Raja clavata is unresolved. This study evaluated the sequence divergence of both the variable control region and cytochrome oxidase I ‘DNA barcode’ gene of the mitochondrial genome to elucidate the genetic differentiation of specimens identified as R. maderensis and R. clavata collected across much of their geographic ranges. Genetic evidence was insufficient to support the different species designations. However regardless of putative species identification, individuals occupying waters around the Azores and North African Seamounts represent an evolutionarily significant unit worthy of special consideration for conservation management.

Changes in epilithic biomasses and invertebrate community structure over a deposit metal concentration gradient in upland headwater streams - Katrina Ann Macintosh; David Griffiths (Hydrobiologia, 2015)

Assessing Landscape Change and Processes of Recurrence, Replacement, and Recovery in the Southeastern Coastal Plains, USA - Mark A. Drummond; Michael P. Stier; Roger F. Auch; Janis L. Taylor; Glenn E. Griffith; Jodi L. Riegle; David J. Hester; Christopher E. Soulard; Jamie L. McBeth (Environmental Management, 2015)

Principles and application of LIMS in mouse clinics - Holger Maier; Christine Schütt; Ralph Steinkamp; Anja Hurt; Elida Schneltzer; Philipp Gormanns; Christoph Lengger; Mark Griffiths; David Melvin; Neha Agrawal; Rafael Alcantara; Arthur Evans; et al. (Mammalian Genome, 2015)

Identification of motivational state in adult male Atlantic walruses inferred from changes in movement and diving behavior - Andrew D. Lowther; Kit M. Kovacs; David Griffiths; Christian Lydersen (Marine Mammal Science, 2015)
Motivational changes in animals are likely to be detectable retrospectively through observed changes in behavior. Breeding represents one of the strongest motivational states in mammals, and its timing is often tied to a seasonally optimal suite of environmental and physical conditions. While seasonal changes in behavior may be directly observable in some species, for others that breed cryptically or in difficult to access areas, detecting behavioral changes may only be feasible using data collected remotely. Herein, we explore whether behavioral changes can be used to infer motivational state for a wild, free‐ and wide‐ranging high arctic marine mammal, adult male Atlantic walruses ( Odobenus rosmarus rosmarus ). Using satellite‐relayed location and dive data from 23 adult male walruses instrumented in the Svalbard Archipelago, we identify seasonal movement to discrete geographic regions deep into winter pack ice. Adult male walrus diving behavior underwent marked seasonal movements between geographical areas that coincided with changes in light regime. At offshore wintering sites adult males ( n = 4) shifted from a summer pattern of deep, long benthic dives to much shallower diving. Some males performed similar shallow, winter dive behavior at coastal locations ( n = 12) suggesting that breeding might also occur around the coast of Svalbard. However, interpretation of behavioral changes of these coastal individuals was challenging. The presumed breeding sites at the winter off‐shore locations were situated in areas where polynyas are known to occur, making them a predictable resource even if they are located deep inside the winter pack‐ice. We demonstrate that remotely collected behavioral data can be used to identify seasonally explicit changes in the behavior of cryptic species.

Long Time Series in US Fisheries Oceanography - Sam McClatchie; Janet Duffy-Anderson; John Field; Ralf Goericke; Dave Griffith; David Hanisko; Jonathan Hare; Joanne Lyczkowski-Shultz; William Peterson; William Watson; Edward Weber; Glenn Zapfe (Oceanography, 2014)

Interpreting environmental change in coastal Alaska using traditional and scientific ecological knowledge - William G. Ambrose; Lisa M. Clough; Jeffrey C. Johnson; Michael Greenacre; David C. Griffith; Michael L. Carroll; Alex Whiting (Frontiers in Marine Science, 2014)

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

Vaccine immunotherapy for prostate cancer: from mice to men - David M. Lubaroff; Daniel Vaena; James A. Brown; Pamela Zehr; Karen C. Griffith; Erica Brown; Julie Eastman; Kenneth Nepple; Ambika Kattula; Richard D. Williams (Immunologic Research, 2014)

Spatial and temporal influences of in-stream factors on the chemistry and epilithic biomasses of upland stream metal deposits - Katrina Ann Macintosh; David Griffiths (Aquatic Sciences, 2014)

High levels of activity of bats at gold mining water bodies: implications for compliance with the International Cyanide Management Code - Stephen R. Griffiths; David B. Donato; Graeme Coulson; Linda F. Lumsden (Environmental Science and Pollution Research, 2014)

Climate and species richness patterns of freshwater fish in North America and Europe - David Griffiths; Chris McGonigle; Rory Quinn (Journal of Biogeography, 2014)
Aim To investigate the effect of climatic, historical and spatial variables on species richness patterns in freshwater fish. Location N orth A merica and E urope. Methods Regional species lists were used to document the spatial richness patterns. Three realms, E urope and P acific and A tlantic N orth A merica, were identified. The numbers of species, by habitat, migration and distributional range categories, were calculated and the contributions of regional mean and seasonal temperature and rainfall, historical (realm, glaciation), and spatial (area, elevational range) variables to predicting richness were assessed using boosted regression trees, model‐averaging and spatially explicit models. Results The latitudinal temperature gradient is stronger than that for rainfall in the A tlantic realm whereas the rainfall gradient in E urope is independent of the temperature gradient. Species richness is more strongly correlated with temperature than rainfall, and the effects are stronger in the A tlantic realm than in E urope. The influence of environmental variables differs between habitat specialist and generalist species. Climate, particularly maximum monthly temperature, is the best predictor of richness in rivers whereas climate variables are less important than historical/spatial variables for diadromous species. Main conclusions Freshwater fish richness differences between realms follow differences in spatial climatic trends. The contributions of climatic, historical and spatial predictor variables vary with ecology: temperature is a better predictor than rainfall in river‐dwellers. The richness gradient is driven more by physiological than by energetic constraints on species. The importance of history is probably underestimated because of correlations with climate variables.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Patterns, processes and vulnerability of Southern Ocean benthos: a decadal leap in knowledge and understanding - Stefanie Kaiser; Simone N. Brandão; Saskia Brix; David K. A. Barnes; David A. Bowden; Jeroen Ingels; Florian Leese; Stefano Schiaparelli; Claudia P. Arango; Renuka Badhe; Narissa Bax; Magdalena Blazewicz-Paszkowycz; et al. (Marine Biology, 2013)

MRI volume of the medial frontal cortex predicts financial capacity in patients with mild Alzheimer’s disease - Luke E. Stoeckel; Christopher C. Stewart; H. Randall Griffith; Kristen Triebel; Ozioma C. Okonkwo; Jan A. den Hollander; Roy C. Martin; Katherine Belue; Jacquelynn N. Copeland; Lindy E. Harrell; John C. Brockington; David G. Clark; et al. (Brain Imaging and Behavior, 2013)

Landscape influences on climate‐related lake shrinkage at high latitudes - Jennifer K. Roach; Brad Griffith; David Verbyla (Global Change Biology, 2013)
Climate‐related declines in lake area have been identified across circumpolar regions and have been characterized by substantial spatial heterogeneity. An improved understanding of the mechanisms underlying lake area trends is necessary to predict where change is most likely to occur and to identify implications for high latitude reservoirs of carbon. Here, using a population of ca. 2300 lakes with statistically significant increasing and decreasing lake area trends spanning longitudinal and latitudinal gradients of ca. 1000 km in A laska, we present evidence for a mechanism of lake area decline that involves the loss of surface water to groundwater systems. We show that lakes with significant declines in lake area were more likely to be located: (1) in burned areas; (2) on coarser, well‐drained soils; and (3) farther from rivers compared to lakes that were increasing. These results indicate that postfire processes such as permafrost degradation, which also results from a warming climate, may promote lake drainage, particularly in coarse‐textured soils and farther from rivers where overland flooding is less likely and downslope flow paths and negative hydraulic gradients between surface water and groundwater systems are more common. Movement of surface water to groundwater systems may lead to a deepening of subsurface flow paths and longer hydraulic residence time which has been linked to increased soil respiration and CO 2 release to the atmosphere. By quantifying relationships between statewide coarse resolution maps of landscape characteristics and spatially heterogeneous responses of lakes to environmental change, we provide a means to identify at‐risk lakes and landscapes and plan for a changing climate.

Magnetic Resonance Spectroscopy of the Normal Cerebellum: What Degree of Variability Can Be Expected? - Stuart Currie; Marios Hadjivassiliou; Iain David Wilkinson; Paul David Griffiths; Nigel Hoggard (The Cerebellum, 2013)

Landscape evolution and engineering geology: results from IAEG Commission 22 - James S. Griffiths; Martin Stokes; Doug Stead; David Giles (Bulletin of Engineering Geology and the Environment, 2012)

A suggested new bacteriophage genus: “Viunalikevirus” - Evelien M. Adriaenssens; Hans-Wolfgang Ackermann; Hany Anany; Bob Blasdel; Ian F. Connerton; David Goulding; Mansel W. Griffiths; Steven P. Hooton; Elizabeth M. Kutter; Andrew M. Kropinski; Ju-Hoon Lee; Martine Maes; et al. (Archives of Virology, 2012)
We suggest a bacteriophage genus, “Viunalikevirus”, as a new genus within the family Myoviridae . To date, this genus includes seven sequenced members: Salmonella phages ViI, SFP10 and ΦSH19; Escherichia phages CBA120 and PhaxI; Shigella phage phiSboM-AG3; and Dickeya phage LIMEstone1. Their shared myovirus morphology, with comparable head sizes and tail dimensions, and genome organization are considered distinguishing features. They appear to have conserved regulatory sequences, a horizontally acquired tRNA set and the probable substitution of an alternate base for thymine in the DNA. A close examination of the tail spike region in the DNA revealed four distinct tail spike proteins, an arrangement which might lead to the umbrella-like structures of the tails visible on electron micrographs. These properties set the suggested genus apart from the recently ratified subfamily Tevenvirinae , although a significant evolutionary relationship can be observed.

Workshop on the ecosystem and fisheries of the Coral Sea: an Australian perspective on research and management - Jock W. Young; A. David McKinnon; Daniela Ceccarelli; Richard Brinkman; Rodrigo H. Bustamante; Mike Cappo; Cathy Dichmont; Peter Doherty; Miles Furnas; Daniel Gledhill; Shane Griffiths; Trevor Hutton; et al. (Reviews in Fish Biology and Fisheries, 2012)

Genome‐wide analysis of longevity in nutrient‐deprived Saccharomyces cerevisiae reveals importance of recycling in maintaining cell viability - Hazel M. Davey; Emma J. M. Cross; Christopher, L. Davey; Konstantinos Gkargkas; Daniela Delneri; David C. Hoyle; Stephen G. Oliver; Douglas B. Kell; Gareth W. Griffith (Environmental Microbiology, 2012)
Summary Although typically cosseted in the laboratory with constant temperatures and plentiful nutrients, microbes are frequently exposed to much more stressful conditions in their natural environments where survival and competitive fitness depend upon both growth rate when conditions are favourable and on persistence in a viable and recoverable state when they are not. In order to determine the role of genetic heterogeneity in environmental fitness we present a novel approach that combines the power of fluorescence‐activated cell sorting with barcode microarray analysis and apply this to determining the importance of every gene in the Saccharomyces cerevisiae genome in a high‐throughput, genome‐wide fitness screen. We have grown > 6000 heterozygous mutants together and exposed them to a starvation stress before using fluorescence‐activated cell sorting to identify and isolate those individual cells that have not survived the stress applied. Barcode array analysis of the sorted and total populations reveals the importance of cellular recycling mechanisms (autophagy, pexophagy and ribosome breakdown) in maintaining cell viability during starvation and provides compelling evidence for an important role for fatty acid degradation in maintaining viability. In addition, we have developed a semi‐batch fermentor system that is a more realistic model of environmental fitness than either batch or chemostat culture. Barcode array analysis revealed that arginine biosynthesis was important for fitness in semi‐batch culture and modelling of this regime showed that rapid emergence from lag phase led to greatly increased fitness. One hundred and twenty‐five strains with deletions in unclassified proteins were identified as being over‐represented in the sorted fraction, while 27 unclassified proteins caused a haploinsufficient phenotype in semi‐batch culture. These methods thus provide a screen to identifying other genes and pathways that have a role in maintaining cell viability.

Body size distributions in North American freshwater fish: large‐scale factors - David Griffiths (Global Ecology and Biogeography, 2012)
Aim To document continental‐ and regional‐scale variation in the size distributions of freshwater fish and examine some energetic, evolutionary and biogeographic explanations for these patterns. Location North America. Methods Regional species lists, coupled with habitat and body size information, were used to document the spatial patterns. Results At the continental scale, riverine specialist fishes show a unimodal, right‐skewed, body size distribution whereas habitat generalist and lacustrine specialist species exhibit bimodal size distributions, with only a slight preponderance of small‐mode species. Most large‐mode species are migratory. Resident species, unlike migratory ones, show a latitudinal increase in mean size, but the size increase across all species is steeper because the importance of large migratory species increases with latitude. Size distributions change from right‐ to left‐skewed with increasing latitude. Maximum body size does not change with increasing family richness but minimum size declines and skewness increases, consistent with diversification of small species. Skewness does not vary with mean family body size. Main conclusions Post‐glacial recolonization by large, habitat generalist, migratory species is the main determinant of latitudinal size distribution trends. There is little support for the energetic hypothesis, but the data are consistent with a negative Cope's rule.

Presence of Arundinaria gigantea (river cane) on numerous non-wetland sites suggests improper ecological classification of the species - Benjamin R. Tanner; David A. Kinner; Adam D. Griffith; Robert S. Young; Lee M. Sorrell (Wetlands Ecology and Management, 2011)

Transport of NOX Emissions from Sugarcane Fertilisation into the Great Barrier Reef Lagoon - Clare Paton-Walsh; Stephen R. Wilson; Travis Naylor; David W. T. Griffith; O. T. Denmead (Environmental Modeling & Assessment, 2011)

Characterisation of polymorphic microsatellite loci in the small-spotted catshark (Scyliorhinus canicula L.) - Andrew M. Griffiths; Didier Casane; Matthew McHugh; Victoria J. Wearmouth; David W. Sims; Martin J. Genner (Conservation Genetics Resources, 2011)

Pharmacodynamic Model of Parathyroid Hormone Modulation by a Negative Allosteric Modulator of the Calcium-Sensing Receptor - Anson K. Abraham; Tristan S. Maurer; Amit S. Kalgutkar; Xiang Gao; Mei Li; David R. Healy; Donna N. Petersen; David A. Griffith; Donald E. Mager (The AAPS Journal, 2011)

Levels of connectivity between longnose skate (Dipturus oxyrinchus) in the Mediterranean Sea and the north-eastern Atlantic Ocean - Andrew M. Griffiths; David W. Sims; Andrew Johnson; Arve Lynghammar; Matthew McHugh; Torkild Bakken; Martin J. Genner (Conservation Genetics, 2011)

Closely related protist strains have different grazing impacts on natural bacterial communities - Edvard Glücksman; Thomas Bell; Robert I. Griffiths; David Bass (Environmental Microbiology, 2010)
Summary Heterotrophic protists are abundant in most environments and exert a strong top‐down control on bacterial communities. However, little is known about how selective most protists are with respect to their bacterial prey. We conducted feeding trials using cercomonad and glissomonad Cercozoa by assaying them on a standardized, diverse bacterial community washed from beech leaf litter. For each of the nine protist strains assayed here, we measured several phenotypic traits (cell volume, speed, plasticity and protist cell density) that we anticipated would be important for their feeding ecology. We also estimated the genetic relatedness of the strains based on the 18S rRNA gene. We found that the nine protist strains had significantly different impacts on both the abundance and the composition of the bacterial communities. Both the phylogenetic distance between protist strains and differences in protist strain traits were important in explaining variation in the bacterial communities. Of the morphological traits that we investigated, protist cell volume and morphological plasticity (the extent to which cells showed amoeboid cell shape flexibility) were most important in determining bacterial community composition. The results demonstrate that closely related and morphologically similar protist species can have different impacts on their prey base.

Climate Change Adaptation for the US National Wildlife Refuge System - Brad Griffith; J. Michael Scott; Robert Adamcik; Daniel Ashe; Brian Czech; Robert Fischman; Patrick Gonzalez; Joshua Lawler; A. David McGuire; Anna Pidgorna (Environmental Management, 2009)

Influence of Outcrop Scale Fractures on the Effective Stiffness of Fault Damage Zone Rocks - W. Ashley Griffith; Pablo F. Sanz; David D. Pollard (Pure and Applied Geophysics, 2009)

Meta-QTL analysis of the genetic control of ear emergence in elite European winter wheat germplasm - Simon Griffiths; James Simmonds; Michelle Leverington; Yingkun Wang; Lesley Fish; Liz Sayers; Leodie Alibert; Simon Orford; Luzie Wingen; Laurence Herry; Sebastien Faure; David Laurie; et al. (Theoretical and Applied Genetics, 2009)

Marine, intertidal, freshwater and terrestrial biodiversity of an isolated polar archipelago - David K. A. Barnes; Stefanie Kaiser; Huw J. Griffiths; Katrin Linse (Journal of Biogeography, 2009)
Aim We ask how biodiverse is a polar archipelago; how this faunal richness is spread across marine, intertidal, freshwater, terrestrial and parasitic realms; and how fast species are accumulated with increased sampling effort. Location The South Orkney Islands (SOI), Scotia Arc, Southern Ocean. Methods We sampled mega‐ and macro‐benthos at the SOI using scuba in the shallows (0–10 m), a rough bottom otter trawl at 150–250 m and an Agassiz trawl and epibenthic sledge, both at depths of 200, 500, 1000 and 1500 m. We also collated species occurrence at the SOI in each realm from a century of literature and modern databases to investigate patterns in species accumulation, endemism, faunistic affinities and bathymetric ranges in three model taxa. Results Our 11 benthic samples showed that point biodiversity at the SOI is high, yielding 19 classes and 158 species. Nearly a third were new to the area, whilst five species and one genus were new to science. The shallowest samples were richest but had fewest new records of species. Known richness at the SOI is dominated by marine species (1026), of which 821 (83.3%) were benthic. Across all realms, 1224 species (50 classes, 24 phyla) were recorded, of which 43 were intertidal, 64 freshwater, 100 terrestrial, 60 parasitic and 40 birds. Species accumulation curves for model taxa showed new sampling yields about 0.75% per sample of known benthic richness, so by Antarctic standards we know the SOI quite well. Most species are Southern Ocean endemics, but very few occur only at the SOI. Main conclusions This first estimate of faunal biodiversity of a polar locality demonstrates both high richness and high levels of knowledge at the SOI. As suspected but never quantified, the benthos dominates polar biodiversity, at least at the SOI. Marine species there constitute 20% of those recently listed for the entire Southern Ocean, whilst > 60% of terrestrial species are known from Antarctica. The SOI, being one of the better‐studied polar locations, of known age and with a discrete shelf, represent an important source of comparison for biodiversity studies. Our data clearly show that richness and our knowledge of the polar fauna differ across environments.

The Turbulent Lagrangian Time Scale in Forest Canopies Constrained by Fluxes, Concentrations and Source Distributions - Vanessa Haverd; Ray Leuning; David Griffith; Eva van Gorsel; Matthias Cuntz (Boundary-Layer Meteorology, 2009)

Directed dispersal of mistletoe (Plicosepalus acaciae) by Yellow-vented Bulbuls (Pycnonotus xanthopygos) - Adam K. Green; David Ward; Megan E. Griffiths (Journal of Ornithology, 2009)

Towards a generalized biogeography of the Southern Ocean benthos - Huw J. Griffiths; David K. A. Barnes; Katrin Linse (Journal of Biogeography, 2009)
Aim To investigate whether the biogeographical regions proposed by J. W. Hedgpeth and widely adopted by other authors hold true, are an oversimplification or with further data might show a unified Antarctic province. Location Southern Hemisphere. Methods The distributions of 1318 species of bivalves, 4656 species of gastropods, 1465 species of cheilostome and 167 species of cyclostome bryozoans were analysed for 29 regions in the Southern Hemisphere, including South American, South African, Tasmanian, New Zealand, sub‐Antarctic and Antarctic regions. We present data on species richness, rates of endemism, patterns of radiation, faunal similarities and multivariate biogeographical analyses. Results The most striking pattern to emerge from our data set of species counts per region was a strong east–west hemispheric asymmetry, with high species numbers in New Zealand, Tasmania and South Africa and low numbers in South America. In contrast, no difference was found in richness between the east and west parts of the Southern Ocean. We compared findings in our model taxa with published data on ascidians, cephalopods and pycnogonids. Further evidence of strong faunal links between the Antarctic and South America is reported in this study, although we found little evidence for a biogeographical relationship between the Antarctic or South America and New Zealand/Tasmania. Strong evidence exists for a long‐term influence of the Antarctic Circumpolar Current upon the distribution of Southern Ocean benthos. This is demonstrated by the reduced prevalence of South American species in the Antarctic and sub‐Antarctic with increasing distance from South America in the direction of the current. Three of our four study taxa (bivalves, cheilostomes and cyclostomes) show the Southern Ocean as a ‘single functional unit’ with no evidence for a biogeographical split between east and west. Main conclusions Unlike the biogeographical schemes previously proposed, we show that biogeographical regions in the Southern Ocean differ depending upon the class of animals being considered. Despite this we suggest that some general rules are viable, including species endemism rates of around 50%, a single Antarctic province and a definite distinction between the sub‐Antarctic islands influenced by South America and those of New Zealand.

Risk remaining from fine particle contaminants after vacuum cleaning of hard floor surfaces - Andrew Hunt; David L. Johnson; J. Brooks; Daniel A. Griffith (Environmental Geochemistry and Health, 2008)

Genes driving potato tuber initiation and growth: identification based on transcriptional changes using the POCI array - Bjorn Kloosterman; David De Koeyer; Rebecca Griffiths; Barry Flinn; Burkhard Steuernagel; Uwe Scholz; Sophia Sonnewald; Uwe Sonnewald; Glenn J. Bryan; Salomé Prat; Zsófia Bánfalvi; John P. Hammond; et al. (Functional & Integrative Genomics, 2008)

Biodiversity and biogeography of southern temperate and polar bryozoans - David K. A. Barnes; Huw J. Griffiths (Global Ecology and Biogeography, 2008)
Aim To describe the distribution of biodiversity and endemism of bryozoans in southern temperate and polar waters. We hypothesized that we would find: (1) no strong latitudinal richness gradient; (2) striking contrasts in richness and endemism between clades and between regions; and (3) that faunal similarity of regions would cluster geographically around each southern continent. Location South Atlantic, Indian and Pacific Oceans and the Southern Ocean. Methods We constructed a data base from known literature, regional data bases and recent finds. We regionalized each southern continent, calculated levels of richness and endemism for each region and continent, and used primer 5 to perform multivariate statistical analysis. Results A third (1681) of global bryozoan species described occur south of 30° S, of which c. 87% were cheilostomes. In richness we found no latitudinal cline and change across longitude was stronger. New Zealand was richest and had the most (60%) endemic species, followed by Antarctica at 57%. There were striking contrasts in regional richness and endemism between clades but the highest levels of between‐region similarity were around Antarctica. The timing of past continent connectivity was reflected. Main conclusions Bryozoans show strong hemispherical asymmetry in richness and, like molluscs and corals, decrease away from Australasia rather than with latitude. Species endemism is much lower in Antarctic bryozoans than previously thought, and as this taxon is not particularly dispersive and is now amongst the best studied regionally, maybe Antarctic endemism in general is lower and Antarctica less cut‐off to species dispersal than previously thought. However, Antarctic generic endemism is double the level previously calculated and regional faunal similarities are much higher than around other continents – both reflecting long‐term isolation. Bryozoans, in contrast to the paradigm of Antarctic fauna, may be fairly robust to predicted climate change. Paradoxically, they may also be one of the best taxa to monitor to sensitively detect marine benthic responses.

A Pseudo-Response Regulator is misexpressed in the photoperiod insensitive Ppd-D1a mutant of wheat (Triticum aestivum L.) - James Beales; Adrian Turner; Simon Griffiths; John W. Snape; David A. Laurie (Theoretical and Applied Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Brain Proton MRS is Correlated with Financial Abilities in Patients with Alzheimer’s Disease - H. Randall Griffith; Ozioma C. Okonkwo; Jan A. den Hollander; Katherine Belue; Sara Lanza; Lindy E. Harrell; John C. Brockington; David G. Clark; Daniel C. Marson (Brain Imaging and Behavior, 2007)

Effects of an increase in summer precipitation on leaf, soil, and ecosystem fluxes of CO2 and H2O in a sotol grassland in Big Bend National Park, Texas - Lisa Patrick; Jessica Cable; Daniel Potts; Danielle Ignace; Greg Barron-Gafford; Alden Griffith; Holly Alpert; Natasja Van Gestel; Traesha Robertson; Travis E. Huxman; John Zak; Michael E. Loik; et al. (Oecologia, 2007)

Potato Expressed Sequence Tag Generation and Analysis using Standard and Unique cDNA Libraries - Barry Flinn; Charlotte Rothwell; Rebecca Griffiths; Martin Lägue; David DeKoeyer; Ravinder Sardana; Patrice Audy; Claudia Goyer; Xiu-Qing Li; Gefu Wang-Pruski; Sharon Regan (Plant Molecular Biology, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Effects of Polyamine Synthesis Inhibitors on Primary Tumor Features and Metastatic Capacity of Human Breast Cancer Cells - Andrea Manni; Sharlene Washington; Xin Hu; James W. Griffith; Richard Bruggeman; Laurence M. Demers; David Mauger; Michael F. Verderame (Clinical & Experimental Metastasis, 2005)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Induced defences in an endangered amphibian in response to an introduced snake predator - Robin D. Moore; Richard A. Griffiths; Cliona M. O’Brien; Adam Murphy; David Jay (Oecologia, 2004)

Fluvial system response to Late Devensian (Weichselian) aridity, Baston, Lincolnshire, England - Rebecca M. Briant; G. Russell Coope; Richard C. Preece; David H. Keen; Steve Boreham; Huw I. Griffiths; Mary B. Seddon; Philip L. Gibbard (Journal of Quaternary Science, 2004)
Little is known about the impact of Late Devensian (Weichselian) aridity on lowland British landscapes, largely because they lack the widespread coversand deposits of the adjacent continent. The concentration of large interformational ice‐wedge casts in the upper part of many Devensian fluvial sequences suggests that fluvial activity may have decreased considerably during this time. The development of optically stimulated luminescence (OSL) dating enables this period of ice‐wedge cast formation to be constrained for the first time in eastern England, where a marked horizon of ice‐wedge casts is found between two distinctive dateable facies associations. Contrasts between this horizon and adjacent sediments show clear changes in environment and fluvial system behaviour in response to changing water supply, in line with palaeontological evidence. In addition to providing chronological control on the period of ice‐wedge formation, the study shows good agreement of the radiocarbon and OSL dating techniques during the Middle and Late Devensian, with direct comparison of these techniques beyond 15 000 yr for the first time in Britain. It is suggested that aridity during the Late Devensian forced a significant decrease in fluvial activity compared with preceding and following periods, initiating a system with low peak flows and widespread permafrost development. Copyright © 2004 John Wiley & Sons, Ltd.

Effects of α-difluoromethylornithine on local recurrence and pulmonary metastasis from MDA-MB-435 breast cancer xenografts in nude mice - Andrea Manni; Sharlene Washington; Laura Craig; Michael Cloud; James W. Griffith; Michael F. Verderame; Lindsay J. Texter; David Mauger; Laurence M. Demers; John F. Harms; Danny R. Welch (Clinical & Experimental Metastasis, 2003)

Development and Evaluation of a Macroinvertebrate Biotic Integrity Index (MBII) for Regionally Assessing Mid-Atlantic Highlands Streams - DONALD J. KLEMM; KAREN A. BLOCKSOM; FLORENCE A. FULK; ALAN T. HERLIHY; ROBERT M. HUGHES; PHILIP R. KAUFMANN; DAVID V. PECK; JOHN L. STODDARD; WILLIAM T. THOENY; MICHAEL B. GRIFFITH; WAYNE S. DAVIS (Environmental Management, 2003)

Laying date and laying sequence influence the sex ratio of crimson rosella broods - Elizabeth Krebs; David Green; Michael Double; Richard Griffiths (Behavioral Ecology and Sociobiology, 2002)

Influence of polyamines on in vitro and in vivo features of aggressive and metastatic behavior by human breast cancer cells - Andrea Manni; Sharlene Washington; James W. Griffith; Michael F. Verderame; David Mauger; Laurence M. Demers; Rajeev S. Samant; Danny R. Welch (Clinical & Experimental Metastasis, 2002)

5,000 year-old spermatozoa in Quaternary Ostracoda (Crustacea) - Renate Matzke-Karasz; David Horne; Horst Janz; Huw Griffiths; William Hutchinson; Richard Preece (The Science of Nature, 2001)

Genetic dissection of collagen-induced arthritis in Chromosome 10 quantitative trait locus speed congenic rats: evidence for more than one regulatory locus and sex influences - Bina Joe; Elaine F. Remmers; David E. Dobbins; Jennifer L. Salstrom; Takefumi Furuya; Svetlana Dracheva; Pércio S. Gulko; Grant W. Cannon; Marie M. Griffiths; Ronald L. Wilder (Immunogenetics, 2000)

Effects of Tuber-borne M-type Strain of Tobacco Rattle Virus on yield and Quality Attributes of Potato Tubers of the Cultivar Wilja - M.F.B. Dale; David J. Robinson; D. Wynne Griffiths; Drummond Todd; Henry Bain (European Journal of Plant Pathology, 2000)

Synonymy of shape Proteocephalus pollanicola Gresson, 1952 (Cestoda: Proteocephalidae), a parasite of pollan, shape Coregonus autumnalis pollan, with shape P. exiguus La Rue, 1911 - Tomáş Scholz; Vladimíra Hanzelová; Ivica Králová; David Griffiths (Systematic Parasitology, 1998)

Problems associated with homogeneity testing in climate variation studies: a case study of temperature in the northern Great Plains, USA - DAVID T. KEISER; JOHN F. GRIFFITHS (International Journal of Climatology, 1997)

Problems associated with homogeneity testing in climate variation studies: a case study of temperature in the northern Great Plains, USA - DAVID T. KEISER; JOHN F. GRIFFITHS (International Journal of Climatology, 1997)